ANALISIS PENGARUH LEVERAGE DAN SIKLUS HIDUP TERHADAP MANAJEMEN LABA PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
Earnings information in general is a major concern in assessing the performance orpersonnel management response and profit information helps owners make anassessment on the earning power in the future. Therefore, the management has atendency to take action that can make a financial report to be well. This researchaims to determine the effect of leverage, firm age, and the sales growth of thepractice of earnings management. The population this research is real estate andproperty companies listed in Indonesia Stock Exchange (IDX). The analytical toolused by using multiple regressions. The results of this study found that Leveragehas a significant influence on Earnings Management. These results indicate that thelower or higher leverage significantly influences the implementation of EarningsManagement Company. While Sales Growth and the Company Age do not havesignificant influence on Earnings Management. These results indicated that thecompany whose sales are up or down does not significantly influence theimplementation of an enterprise Earnings Management and Corporate Age (AGE) isnot a determinant of the presence of Earnings Management implementation within acompany. Coefficient determination of 22.2% or 0.222, meaning that 22.2% of thedependent variable is affected by the independent variable, while 77.8% areinfluenced by variables beyond the variables studied in this research.Keywords: Leverage, corporate age, growth sales, and earnings management